Analisis Manajemen Perubahan dan Budaya Organisasi dalam Meningkatkan Mutu Pendidikan Agama Islam - Royhan Iqbal; Ali Nurhadi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
Abstract Culture will continue to develop and change in line with the times, the acceleration of the development of science and technology, as well as the development of human intelligence, It is necessary to have an organizational culture in the performance group, especially qualified individuals to become quality educational institutions. In the introduction we give an understanding of what is meant by organizational culture in an educational environment and give when the emergence of culture and organizations, The term culture can be interpreted as the totality of patterns of behavior, art, beliefs, institutions, and all other products of human work and thought that characterize the conditions of a society or population transmitted together.